Introduction and early measurement of carbon footprint concepts to respond the challenge of SDGs-Goal 13 - Santhyami, S.; Al Mubarok, Moh. Isna; Nurzahra, Vakha Yulia (Universitas Muhammadiyah Malang, 2020)
One of the efforts to prevent the effects of climate change was the introduction of the concept of carbon footprints from an early age to students. Science subjects in this school have included elements of environmental knowledge in their subject matter. However, mitigation and adaptation efforts to climate change were still lacking recognition. The purpose of this study was to introduce and measure the extent to which elementary students are able to recognize the concept of carbon footprints and can use a simple carbon footprint calculator application in climate change mitigation and adaptation efforts. The study was conducted at MIM Kupang Karangdowo Klaten, Central Java. The activity was carried out on February 19, 2020 with the method of lectures, interviews, and simulations, followed by 11 teachers and 21 grade VI students. The flow of activities was divided into 3, namely: (1) counseling/explanation of the carbon cycle, global warming, carbon footprint and carbon footprint calculator, (2) interviews about the student's daily and weekly lifestyle or carbon footprint pattern, (3) socialization of the footprint calculator application carbon and usability observations. The activity ended with a simulation of a carbon footprint calculator for several students. From the study conducted, it can be seen that students are interested in this carbon footprint concept and were technically assessed as being able to use a carbon calculator without significant obstacles.